Severe preeclampsia and eclampsia: incidence, complications, and perinatal outcomes at a low-resource setting, Mpilo Central Hospital, Bulawayo, Zimbabwe - Ngwenya S (Dove Medical Press, 2017)
Solwayo Ngwenya1–3 1Department of Obstetrics & Gynaecology, Mpilo Central Hospital, 2Department of Obstetrics & Gynaecology, Royal Women’s Clinic, 3National University of Science and Technology, Medical School, Bulawayo, Matabeleland, Zimbabwe Background: Severe preeclampsia is a disorder of pregnancy characterized by high blood pressure and significant proteinuria after 20 weeks gestation. Severe preeclampsia and eclampsia have considerable adverse impacts on maternal, fetal, and neonatal health especially in low-resource countries. Hypertensive disorders of pregnancy are the third leading cause of maternal deaths in Sub-Saharan Africa. Significant avoidable maternal and neonatal morbidity and mortality may result.Objectives: This study aimed 1) to determine the incidence of severe preeclampsia/eclampsia in a low-resource setting; 2) to determine the maternal complications of severe preeclampsia/eclampsia in a low-resource setting; 3) to determine the perinatal outcomes of severe preeclampsia/eclampsia in a low-resource setting.Methods: This was a retrospective descriptive cohort study carried out at Mpilo Central Hospital, a tertiary teaching referral government hospital in a low-resource setting in Bulawayo, Zimbabwe. Data were obtained from the birth registers in labor ward, intensive care unit, and neonatal intensive care unit of patients who had a diagnosis of severe preeclampsia or eclampsia for the period January 1, 2016, to December 31, 2016. The case notes were retrieved and the demographic, clinical, and outcome data were gathered.Results: There were 9,086 deliveries at the institution during the period January 1, 2016, to December 31, 2016. There were 121 cases of severe preeclampsia/eclampsia. The incidence of severe preeclampsia/eclampsia was 1.3% at Mpilo Central Hospital. The most common major complication was HELLP syndrome (9.1%). Maternal mortality was 1.7%. There were 127 babies born with six sets of twins, 49.6% of the babies were lost through stillbirths and early neonatal deaths.Conclusion: The incidence of severe preeclampsia/eclampsia at Mpilo Central Hospital was 1.3%. The most common maternal complication was hemolysis elevated liver enzymes low platelet syndrome. Maternal mortality was 1.7% due to acute renal failure. Nearly half (49.6%) of the babies born were lost to stillbirths and early neonatal deaths. Keywords: severe preeclampsia, eclampsia, mortality, morbidity, perinatal outcomes, low-resource settings, Mpilo Central Hospital